2021
DOI: 10.1111/ctr.14529
|View full text |Cite
|
Sign up to set email alerts
|

Comparing weight‐based dosing of tacrolimus XR in obese and non‐obese renal transplant recipients

Abstract: The recommended initial weight-based dose of extended-release (XR) tacrolimus (Envarsus XR) in kidney transplant recipients (KTR) is 0.14 mg/kg/day. However, no data exist regarding dosing recommendations for obese patients specifically. The aim of this study was to evaluate weight-based dosing requirements in a cohort of obese KTR who were initiated on de novo tacrolimus XR post-transplantation. The primary outcome was weight-based dosing requirements (mg/kg/day) on post-operative day (POD) 7 and 14. Of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 10 publications
(9 reference statements)
2
11
0
Order By: Relevance
“…This finding was consistent across all groups 9 . Additionally, a larger proportion of patients with BMI > 30 kg/m 2 had supratherapeutic trough levels and BMI was found to be independently associated with the higher trough levels 9 . This differs from our study which showed that utilizing IBW in obese patients led to initial underdosing; however, should be noted that our obese population had a mean weight of 100.5 kg.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This finding was consistent across all groups 9 . Additionally, a larger proportion of patients with BMI > 30 kg/m 2 had supratherapeutic trough levels and BMI was found to be independently associated with the higher trough levels 9 . This differs from our study which showed that utilizing IBW in obese patients led to initial underdosing; however, should be noted that our obese population had a mean weight of 100.5 kg.…”
Section: Discussionsupporting
confidence: 72%
“…9 IBW led to no difference in therapeutic doses between the BMI groups on post-op day (POD) 7 with similar findings on POD 14. 9 Obesity in solid organ transplant is associated with higher incidence of DGF, acute rejection, metabolic complications, and mortality so it is crucial to ensure appropriate dosing of tacrolimus. 10 Therefore, the objectives of this study were to assess the conversion ratio from IR to LCP tacrolimus in obese kidney transplant recipients, defined as a BMI of ≥30 kg/m 2 and assess the impact of BMI and ideal body weight (IBW), total body weight (TBW), and adjusted body weight (AdjBW) on IR and LCP mg/kg dosing at steady state therapeutic goal.…”
supporting
confidence: 60%
See 3 more Smart Citations